Mary Anne's bad-luck mystery - Martin, Ann M., 1955- (New York : Scholastic, 1988)
Ever since Mary Anne threw away the chain letter she got in the mail, bad things have been happening to everybody in the Baby-sitters Club.
"An Apple paperback.".
6.0
3-6
Keywords: Babysitters -- Fiction; Letters -- Fiction; Babysitters -- Fiction; Letters -- Fiction